2013
DOI: 10.3382/ps.2012-02554
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid requirements of broiler breeders at peak production for egg mass, body weight, and fertility

Abstract: Two trials were conducted to determine the amino acid and protein requirements of broiler breeders at peak production. In trial 1, 32-wk-old Cobb 500 broiler breeders with similar BW were selected to determine the digestible amino acid requirement for daily product output (g of egg mass + g of BW gain/b/d) and feed conversion (g of feed/g of product) for Met, Phe, Arg, Ile, Lys, and CP in a 42-d production study. In trial 2, 30-wk-old Cobb 500 broiler breeders were selected to determine the digestible requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…One thing we can see that the requirements determined for maximum productivity in the present study (average 925 mg) are considerably higher than those from previous researches. These results closely in accordance with recent results worked by Ekmay et al (2013), who Fig. 1.…”
Section: Resultssupporting
confidence: 83%
“…One thing we can see that the requirements determined for maximum productivity in the present study (average 925 mg) are considerably higher than those from previous researches. These results closely in accordance with recent results worked by Ekmay et al (2013), who Fig. 1.…”
Section: Resultssupporting
confidence: 83%
“…It has been verified that the concentration of lysine in plasma can decrease with increase of dietary isoleucine concentration (Peganova & Eder, 2003). It is suggested that excess dietary isoleucine may affect fertility of broiler breeders (Ekmay et al, 2013) and that the digestible isoleucine:lysine ratio affects feed conversion and breast meat yield in broilers (Mejia et al, 2011). The studies on isoleucine requirement for broilers have been reviewed; however, there are limited recent studies assessing isoleucine requirements and isoleucine: lysine ratio for laying hens in the egg-laying phase.…”
Section: Introductionmentioning
confidence: 95%
“…Van Emous et al (2018) noted that during phase 1 (22: 34wks) and phase 2 (35: 46 wks) fertility and hatchability was not affected by reductions in dietary crude protein levels (13 to 11.5%). Some authors did not observe an effect of dietary protein levels on incubation traits (Mejia et al, 2012), although others showed that feeding poultry breeders a high protein levels during the laying period decreased fertility (Ekmay et al, 2013). Wilson et al (1988) showed no effect of feeding 9, 12 or 15% protein were observed on semen volume, concentration, number of spermatozoa ejaculated or spermatogenic activity.…”
Section: Resultsmentioning
confidence: 99%